Prevalence and Burden of Dyspnoea Among Patients with Chronic Obstructive Pulmonary Disease in Five European Countries. Issue 1 (June 2016) - Punekar, Yogesh; Mullerova, Hana; Small, Mark; Holbrook, Tim; Wood, Robert; Naya, Ian; Valle, Manuel
Abstract Introduction Dyspnoea is a common symptom of chronic obstructive pulmonary disease (COPD) that has a significant direct impact on patients' respiratory health status and contributes substantially to the economic burden of the disease. The objective of this study was to report on the prevalence of dyspnoea and its cost impact among patients with COPD in five European countries (France, Germany, Italy, Spain and the UK). Methods A population-based cross-sectional survey (Respiratory Disease-Specific Programme, Adelphi Real World) was conducted among 2531 patients with COPD and their treating physicians. Information was collected on demographic and clinical characteristics, dyspnoea [modified Medical Research Council (mMRC) scale], health status [COPD Assessment Test (CAT), EuroQol (EQ-5D-3L)], sleep [Jenkins Sleep Evaluation Questionnaire (JSEQ)], and healthcare resource use including moderate-to-severe COPD exacerbations, physician visits, COPD medications, and other COPD-related resources. The humanistic and economic burden was derived from two cohorts based on their level of dyspnoea (mMRC <2 vs. mMRC ≥2) who were matched by propensity scores to balance their demographic and disease burden characteristics. Results Moderate-to-severe dyspnoea (mMRC ≥2) was highly prevalent across all countries, ranging from 39.5% in France to 60.2% in the UK. Overall in the unmatched cohorts, mMRC ≥2 (n  = 1199) was associated with more comorbidities and more frequent exacerbations (> 2/year) compared to patients with mMRC <2 (n  = 1332). Descriptive analysis indicated that the patient cohort with worse dyspnoea had poorer health status (CAT: 25.1 vs. 16.2;P  < 0.0001), poorer sleep (JSEQ: 7.1 vs. 3.8;P  < 0.0001), and poorer quality of life (EQ-5D-3L: 0.66 vs. 0.88;P  < 0.0001). These findings were replicated in each of the five EU countries. In the propensity score-matched population balanced for non-dyspnoeic severity parameters, patients with worse dyspnoea had significantly higher annual costs for COPD management (€4372 vs. €2031, P  < 0.0001). Conclusion Moderate-to-severe dyspnoea is highly prevalent in patients with COPD across the five European countries studied. It is associated with a significant disease burden and more than doubles the economic burden on health care systems. Funding GlaxoSmithKline (Study number HO-15-15223).